Development of a loop-mediated isothermal amplification assay for the rapid detection of Russula subnigricans and Russula japonica - Long, Pan; Jiang, Zijuan; He, Zhengmi; Chen, Zuohong (Frontiers in Microbiology, 2022)
Russula subnigricans is the only lethal species in Russula with its mortality greater than 50% and R. japonica is the most common poisonous species which makes it of vital importance to realize rapid species identification in mushroom poisoning incidents. The main objective of this study was to develop a rapid, specific, sensitive and simple loop-mediated isothermal amplification (LAMP) assay for the detection of R. subnigricans and R. japonica. Two sets of species-specific LAMP primers targeting internal transcribed spacer (ITS) regions were designed to identify R. subnigricans and R. japonica. The results demonstrated that LAMP could specifically detect R. subnigricans and R. japonica, while PCR could not distinguish R. subnigricans from R. nigricans. In addition, the results demonstrated that the detection sensitivity of HNB-LAMP (LAMP mixture with HNB dye) for R. subnigrican was comparative with Electrophoresis-LAMP and RT-qLAMP, which was able to reach 0.5 pg/μL and 100 times higher than that of PCR. The reaction of LAMP was able to finish in 45 min, which was far less than conventional PCR. LAMP holds the potential to be a quick, specific and sensitive detection tool in various fields in the future.